Experimental analysis and numerical simulation for biodegradability of polyethylene - Kawai, Fusako; Watanabe, Masaji; Shibata, Masaru; Yokoyama, Shigeo; Sudate, Yasuhiro (Polymer Degradation and Stability, 2002)
Biodegradability of polyethylene wax (PEwax) was studied both experimentally and analytically. The weight loss of PEwax (0.5%) by a microbial consortium in approximately 3 weeks was 31.5% and the top molecular weights shifted to higher values. One of the features observed experimentally was fast consumption of low molecular weight-PEwax. On the other hand, one may speculate, theoretically, that hydrocarbons such as PE should be subject to an initial oxidation to yield carboxylated compounds at their terminals, which are then depolymerized via β-oxidation process. A mathematical model based on these theoretical and experimental aspects is proposed and a method of analysis is illustrated. β-Oxidation rates and consumption rates of low molecular weight-PEwax are determined numerically, and the temporal change of weight distribution is simulated. Numerical results are compared with experimental results, and the governing mechanism of biodegradation is interpreted. We conclude that the primary factors in biodegradation of polyethylene are an initial oxidation at the terminals of molecules followed by β-oxidation and consumption of low molecular weight-PEwax. The most reliable biodegradation limit was approx. 2000.